Penelitian Tindakan Kelas Berbasis Kolaborasi (Analisis Prosedur, Implementasi dan Penulisan Laporan) - Syahrul Sitorus (AUD Cendekia, 2022)
This study aims to analyze the procedures, implementation and writing of collaboration-based classroom action research reports. This research was conducted using library research-based research methods, with data analysis techniques using descriptive analysis techniques. The results of the study explain that the classroom action research procedure begins with the procedure for identifying learning problems encountered in the classroom by educators, then formulating problems, planning research, determining research instruments, conducting research, analyzing data and writing reports. Implementation is carried out through four stages, namely planning, implementation, observation, and follow-up. This implementation is carried out by teachers in collaboration with teaching teachers or involving other parties as teachers. The CAR report is basically not much different from other research, it's just that the description in the CAR research is more descriptive.